Benefits of Acoustic Beamforming for Solving the Cocktail Party Problem - Gerald Kidd; Christine R. Mason; Virginia Best; Jayaganesh Swaminathan (Trends in Hearing, 2015)
The benefit provided to listeners with sensorineural hearing loss (SNHL) by an acoustic beamforming microphone array was determined in a speech-on-speech masking experiment. Normal-hearing controls were tested as well. For the SNHL listeners, prescription-determined gain was applied to the stimuli, and performance using the beamformer was compared with that obtained using bilateral amplification. The listener identified speech from a target talker located straight ahead (0° azimuth) in the presence of four competing talkers that were either colocated with, or spatially separated from, the target. The stimuli were spatialized using measured impulse responses and presented via earphones. In the spatially separated masker conditions, the four maskers were arranged symmetrically around the target at ±15° and ±30° or at ±45° and ±90°. Results revealed that masked speech reception thresholds for spatially separated maskers were higher (poorer) on average for the SNHL than for the normal-hearing listeners. For most SNHL listeners in the wider masker separation condition, lower thresholds were obtained through the microphone array than through bilateral amplification. Large intersubject differences were found in both listener groups. The best masked speech reception thresholds overall were found for a hybrid condition that combined natural and beamforming listening in order to preserve localization for broadband sources.